Polymorphism and Fast Potassium‐Ion Conduction in the T5 Supertetrahedral Phosphidosilicate KSi2P3. Issue 24 (7th May 2021) - Haffner, Arthur; Hatz, Anna‐Katharina; Zeman, Otto E. O.; Hoch, Constantin; Lotsch, Bettina V.; Johrendt, Dirk
Abstract: The all‐solid‐state battery (ASSB) is a promising candidate for electrochemical energy storage. In view of the limited availability of lithium, however, alternative systems based on earth‐abundant and inexpensive elements are urgently sought. Besides well‐studied sodium compounds, potassium‐based systems offer the advantage of low cost and a large electrochemical window, but are hardly explored. Here we report the synthesis and crystal structure of K‐ion conducting T5 KSi2 P3 inspired by recent discoveries of fast ion conductors in alkaline phosphidosilicates. KSi2 P3 is composed of SiP4 tetrahedra forming interpenetrating networks of large T5 supertetrahedra. The compound passes through a reconstructive phase transition from the known T3 to the new tetragonal T5 polymorph at 1020 °C with enantiotropic displacive phase transitions upon cooling at about 155 °C and 80 °C. The potassium ions are located in large channels between the T5 supertetrahedral networks and show facile movement through the structure. The bulk ionic conductivity is up to 2.6×10 −4 S cm −1 at 25 °C with an average activation energy of 0.20 eV. This is remarkably high for a potassium ion conductor at room temperature, and marks KSi2 P3 as the first non‐oxide solid potassium ion conductor. Abstract : Size matters: Only a structure with large T5 supertetrahedra enables fast K + ‐ion conduction in the polymorphic phosphidosilicate KSi2 P3 .